Evaluation of Acid Mine Drainage Neutralization Using CaO and Alum - Ridho Yovanda; Audrey Faiza Rosa; Finny Marsyah; Wiya Elsa Fitri; Adewirli Putra (JURNAL KATALISATOR, 2026)
Acid mine drainage (AMD) is a major environmental issue associated with coal mining activities, characterized by low pH and elevated concentrations of dissolved metals that can degrade water quality and harm aquatic ecosystems. Active treatment using alkaline materials such as quicklime (CaO) combined with coagulants like alum is widely applied to neutralize acidity and reduce metal content. This study aims to evaluate the effectiveness of CaO and alum in improving the pH of acid mine drainage. The research was conducted through a combination of field testing and laboratory analysis. The treatment process involved dosing quicklime and alum into acid mine drainage, followed by periodic pH measurements at inlet and outlet points over a one-month observation period. Data were analyzed using linear regression to determine the relationship between CaO dosage and pH changes. The results showed that the initial pH of acid mine drainage remained acidic, with an average value of 4.43, and increased slightly within the range of 4.43 to 4.76 after treatment. Regression analysis indicated a strong correlation (R² = 0.9537) between CaO dosage and pH increase, suggesting that higher dosages contribute to improved neutralization performance. However, the achieved pH values have not yet met the environmental quality standard (pH ≥ 6), indicating that further optimization of treatment dosage and process conditions is required. These findings highlight that while the combination of CaO and alum has potential in neutralizing acid mine drainage, its current application is not yet sufficient to achieve regulatory compliance and improvements in treatment design are necessary.